2013
DOI: 10.1038/nsmb.2637
|View full text |Cite
|
Sign up to set email alerts
|

Nα-acetylated Sir3 stabilizes the conformation of a nucleosome-binding loop in the BAH domain

Abstract: In Saccharomyces cerevisiae, acetylation of the Sir3 N terminus is important for transcriptional silencing. This covalent modification promotes the binding of the Sir3 BAH domain to the nucleosome, but a mechanistic understanding of this phenomenon is lacking. By X-ray crystallography, we show here that the acetylated N terminus of Sir3 does not interact with the nucleosome directly. Instead, it stabilizes a nucleosome-binding loop in the BAH domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 25 publications
2
47
0
Order By: Relevance
“…23 Furthermore, the importance of H4-K16 for Sir3 nucleosomal recognition has been highlighted by several high-resolution structures of Sir3-nucleosome complexes. 19,2426 These studies demonstrate that H4-K16 occupies a central cavity within the nucleosome binding domain of Sir3, consistent with previous biochemical data showing that high affinity binding of Sir3 to histone peptides 27 and to mononucleosomes is disrupted by H4-K16 acetylation or glutamine substitution. 9,28 These results contrast with several in vitro studies indicating that Sir3 has a high nonspecific binding affinity for DNA, 21,22 and that the binding of Sir3 to 6-mer nucleosomal arrays is relatively insensitive to a H4-K16Q substitution.…”
supporting
confidence: 90%
“…23 Furthermore, the importance of H4-K16 for Sir3 nucleosomal recognition has been highlighted by several high-resolution structures of Sir3-nucleosome complexes. 19,2426 These studies demonstrate that H4-K16 occupies a central cavity within the nucleosome binding domain of Sir3, consistent with previous biochemical data showing that high affinity binding of Sir3 to histone peptides 27 and to mononucleosomes is disrupted by H4-K16 acetylation or glutamine substitution. 9,28 These results contrast with several in vitro studies indicating that Sir3 has a high nonspecific binding affinity for DNA, 21,22 and that the binding of Sir3 to 6-mer nucleosomal arrays is relatively insensitive to a H4-K16Q substitution.…”
supporting
confidence: 90%
“…Sir3 crystal structures indicate that N-terminal acetylation of this protein mediates the formation of a fine structural element that are required for function. 45,46 Notably, the mating defect associated with loss of Sir3 N-terminal acetylation can be partially suppressed by overexpression of the Hsp70 chaperone Ssb1. 20 Moreover, mutations in Sir3 that synergize with disruption of NatA to promote a more severe mating defect (E131K, T135I, L208S, S813R) 47 are predicted to alter aggregation potential and/or disorder in Sir3 (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies suggested and biochemical studies proved that Sir3 N a acetylation increases the affinity of Sir3 for nucleosomes (Connelly et al 2006;Onishi et al 2007;van Welsem et al 2008;Sampath et al 2009). Crystallographic studies showed that the Sir3 modification stabilizes the surface of the Sir3 BAH domain at the nucleosome-binding interface (Arnaudo et al 2013;Yang et al 2013).…”
Section: Post-and Cotranslational Modification Of Sir3mentioning
confidence: 99%